Performance of ImproGene Cell-Free DNA Tubes for Stabilization and Analysis of cfDNA in Blood Samples. (3rd September 2022) - Luo, Jianglan; Wang, Sina; Zhang, Shu; He, Ye; Li, Siyun; Han, Jianhong; Xu, Mingfei; Deng, Guanhua
Abstract: Background: With the development of liquid biopsy technology, the demand for noninvasive prenatal testing (NIPT) is increasing rapidly. The aim of the study is to evaluate the effects of different blood collection tubes on plasma cfDNA and NIPT quality control. Methods: We investigated hemolysis, cfDNA concentration, and fragment distribution within blood samples stored in EDTA, ImproGene, and Streck tubes. The effects of ImproGene and Streck tubes on NIPT quality control were evaluated. Results: The ImproGene tubes prevented the time-dependent increase of cfDNA concentration and preserved the cfDNA fragment size distribution. For NIPT quality control, there is no significant difference in cfDNA, library concentration, and fetal fraction between ImproGene and Streck tubes samples. GC content of the samples in ImproGene tubes was closer to the human genome. Conclusion: The ImproGene cfDNA tube has excellent performance and is an effective choice for storing blood samples for NIPT testing or other cfDNA analysis.